146. antifungal Susceptibility Patterns of candida Parapsilosis Bloodstream Isolates in the US, 2008–2018. (31st December 2020) - Tesini, Brenda L; Lyman, Meghan; Jackson, Brendan R; Gellert, Anita; Schaffner, William; Farley, Monica M; Shrum, Sarah; Phipps, Erin C; Zhang, Alexia Y; Pattee, Brittany; Fischer, Jill; Johnston, Helen; et al.
Abstract: Background: Multidrug resistant Candida is an increasing concern. C. parapsilosis in particular has decreased in vitro susceptibility to echinocandins. As a result, fluconazole had been favored for C. parapsilosis treatment. However, there is growing concern about increasing azole resistance among Candida species. We report on antifungal susceptibility patterns of C. parapsilosis in the US from 2008 through 2018. Methods: Active, population-based surveillance for candidemia through the Centers for Disease Control and Prevention's (CDC) Emerging Infections Program was conducted between 2008–2018, eventually encompassing 9 states (GA, MD, OR, TN, NY, CA, CO, MN, NM). Each incident isolate was sent to the CDC for species confirmation and antifungal susceptibility testing (AFST). Frequency of resistance was calculated and stratified by year and state using SAS 9.4 Results: Of the 8, 704 incident candidemia isolates identified, 1, 471 (15%) were C. parapsilosis ; the third most common species after C. albicans and C. glabrata . AFST results were available for 1, 340 C. parapsilosis isolates. No resistance was detected to caspofungin (MIC50 0.25) or micafungin (MIC50 1.00) with only one (< 1%) isolate resistant to anidulafungin (MIC50 1.00). In contrast, 84 (6.3%) isolates were resistant to fluconazole and another 44 (3.3%) isolates had dose-dependent susceptibility to fluconazole (MIC50 1.00). Fluconazole resistance increased sharply from an average of 4% during 2008–2014 to a peak of 14% in 2016 with a subsequent decline to 6% in 2018 (see figure). Regional variation is also observed with fluconazole resistance ranging from 0% (CO, MN, NM) to 42% (NY) of isolates by site. Conclusion: The recent marked increase in fluconazole resistance among C. parapsilosis highlights this pathogen as an emerging drug resistant pathogen of concern and the need for ongoing antifungal resistance surveillance among Candida species. Our data support the empiric use of echinocandins for C. parapsilosis bloodstream infections and underscore the need to obtain AFST prior to fluconazole treatment. Furthermore, regional variation in fluconazole resistance emphasizes the importance of understanding local Candida susceptibility patterns. Disclosures: Lee Harrison, MD, GSK (Consultant)Merck (Consultant)Pfizer (Consultant)Sanofi Pasteur (Consultant)